Hollow tubular porous covalent organic framework (COF) nanostructures1. Issue 58 (25th July 2015) - Pachfule, Pradip; Kandmabeth, Sharath; Mallick, Arijit; Banerjee, Rahul
<x xml:space="preserve">Abstract</x> Hollow and tubular TpPa-COF structures with high chemical stability and porosity have been synthesized by template-assisted replication of nanometer sized ZnO-nanorods.